How to Improve Elementary School Student Learning Outcomes by Implementing the Articulation Type Cooperative Learning Model? - Indrawati, Naili; Desky, Anggi Yulia Didri (Journal of Indonesian Primary School, 2024)
Islamic education learning at the elementary school level is one type of learning that focuses on instilling students' spiritual values. This research aims to improve elementary school students' learning outcomes in Islamic religious education learning by implementing an articulation type cooperative model. This research uses a classroom action research method with a Kemmis & Mc Taggart design. This research step in each cycle consists of four, namely planning, action, observation and reflection. The subjects of this research were fourth grade elementary school students. Data was collected using observation and test techniques. The research results show that the application of the articulation type cooperative model can improve student learning outcomes in Islamic religious education learning in elementary schools. Therefore, this learning model can be used as an alternative solution to the problem of low student learning outcomes in Islamic religious education learning in elementary schools.